Fluidization in insect constructions in soils - Genise, Jorge Fernando (2000)
Fluidization, a special case of liquefaction, is a physical process occurring in unconsolidated, water-saturated, sediments that can be verified in insect constructions in soils. Behavioral analysis of the bees Ptilothrix relata and Diadasina distincta shows that the fine-grained material of the soil pellets, utilized to construct the chimneys and cells of the nest, have been subjected to fluidization. The increment of pore pressure transmited by the bee’s appendages to the moulded soil pellets, produces the outward escape of water, which drags the fine-grained material. Micromorphologically, the fluidization is reflected in the thin layers of clay and organic matter deposited on those surfaces of the constructions exposed to direct contact with the bee’s appendages and in the higher content of fine-grained material close to these layers. Along with the reorientation of the coarser grains of the soil, produced also by the moulding behavior of the bee, these micromorphological features, having high preservational potential, constitute important ichnotaxobases and valuable clues to aid in the recognition of insect trace fossils in paleosols.